Norcantharidin Inhibits SK-N-SH Neuroblastoma Cell Growth by Induction of Autophagy and Apoptosis. (February 2017) - Han, Zeping; Li, Baoxia; Wang, Juanjuan; Zhang, Xiangqiang; Li, Zhenhua; Dai, Liting; Cao, Mingrong; Jiang, Jianwei
Norcantharidin, a low-toxic analog of the active anticancer compound cantharidin in Mylabris, can inhibit proliferation and induce apoptosis of multiple types of cancer cells. However, the anticancer activities of norcantharidin with respect to neuroblastoma, and its underlying mechanisms, have not been investigated. Therefore, our study was designed to determine the efficacy of norcantharidin on SK-N-SH neuroblastoma cell death and to elucidate detailed mechanisms of activity. In the present study, norcantharidin suppressed the proliferation and cloning ability of SK-N-SH cells in a dose-dependent manner, apparently by reducing the mitochondrial membrane potential and arresting SK-N-SH cells at the G2/M stage, accompanied by elevated expressions of p21 and decreased expressions of cyclin B1 and cell division control 2. Treatment by norcantharidin induced significant mitophagy and autophagy, as demonstrated by a decrease in Translocase Of Outer Mitochondrial Membrane 20 (TOM20), increased beclin1 and LC3-II protein expression, reduced protein SQSTM1/p62 expression, and accumulation of punctate LC3 in the cytoplasm of SK-N-SH cells. In addition, norcantharidin induced apoptosis through regulating the expression of B-cell lymphoma 2–associated X protein/B-cell lymphoma 2 and B-cell lymphoma 2–associated X protein/myeloid cell leukemia 1 and activating caspase-3 and caspase-9–dependent endogenous mitochondrial pathways. We also observed an increase in phosphor–AMP-activated protein kinase accompanied with a decrease in phosphor-protein kinase B and mammalian target of rapamycin expression after treatment with norcantharidin. Subsequent studies indicated that norcantharidin participates in cellular autophagy and apoptosis via activation of the c-Jun NH2-terminal kinases/c-Jun pathway. In conclusion, our results demonstrate that norcantharidin can reduce the mitochondrial membrane potential, induce mitophagy, and subsequently arouse cellular autophagy and apoptosis; the AMP-activated protein kinase, protein kinase B/mammalian target of rapamycin, and c-Jun NH2-terminal kinases/c-Jun signaling pathways are widely involved in these processes. Thus, the traditional Chinese medicine norcantharidin could be a novel therapeutic strategy for treating neuroblastoma.